The Development of Discovery Learning Model Teaching Materials to Improve Students’ Mathematical Problem Solving Ability on Junior High School - Marthalita, Mona; Kadarisma, Gida; Afrilianto, M. ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
In order to enhance students' mathematical problem-solving skills, this study looks at how teaching materials are developed using the Discovery Learning model. Since every student nowadays needs to be able to think critically, the study specifically looks at the process and outcomes. development, viability testing, feedback from students, and improving mathematical problem-solving skills. This kind of research makes use of the Research and Development (R&D) or Research-based Development research method, which is a way to create a specific product and use a model to test the product's viability. Students in class VII at MTs Al Bidayah West Bandung Regency served as the research sample for S. Thiagarajan's 4D (Define, Design, Develop, and Disseminate) study. The process and outcomes of creating educational materials lead to the conclusion that the materials, when viewed from the various stages, follow the procedures or methods outlined in 4D. Based on students' responses, which were 68.4% and 70.2% in the good category, the viability of teaching materials made possible by the Photoshop program can be concluded, along with the students' improved problem-solving skills. If this teaching material is used in a classroom setting, it is imperative that the necessary facilities be set up ahead of time because learning with it requires sufficient facilities. There are tasks and content in this teaching resource that need to be altered. so that students' learning experiences are not dull and monotonous.